The Polity of Regional Integration Development and the Challenges Hampering Southern Africa Economic Growth - Enaifoghe, Andrew; Mkhwanazi, Sandile Blessing (Journal of Economics and Behavioral Studies, 2020)
This paper explored the polity of regional integration development and the challenges hampering the southern Africa economic growth. The study finds that the design and structure of the African regional development within the integration schemes is around inward-looking industrialization that is intended to facilitate economic costs of participation for member states. This often remains unevenly distributed among member states. Most countries in Africa linger highly reliant on agriculture and yet suffer from high levels of unemployment and food insecurity in the continent. In these situations, it is logical for one to expect the “African regional integration in the Southern African Development Community (SADC) sub-regional schemes to be most focused on developing whatsoever synergies that may exist to promote both socio-economic development and regional security across borders, which may hamper the policy implementation through good governance and ethical valued approach. Qualitatively, this paper collected data and analysis them based on content, using secondary sources from different domains, including Google scholars, Scorpius repositories.